1996
DOI: 10.1097/00006534-199606000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Tissue Fungal Infections: Surgical Management of 12 Immunocompromised Patients

Abstract: Isolated fungal soft-tissue infections are uncommon but may cause severe morbidity or mortality among transplant recipients and other immunosuppressed patients. Twelve immunocompromised patients illustrating three patterns of infection were treated recently at the Duke University Medical Center. These groups comprised (I) locally aggressive infections, (II) indolent infections, and (III) cutaneous manifestations of systemic infection. Patient diagnoses included organ transplant, leukemia, prematurity, chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 21 publications
0
55
0
Order By: Relevance
“…An exception may be in patients with hematologic disorders in which neutropenia may be reversed. Successful treatment of primary cutaneous aspergillosis associated with neutropenia has been associated with reversal of neutropenia by use of granulocyte colony-stimulating factor (G-CSF) (115). Amphotericin preparations or voriconazole would be the preferred initial therapy.…”
Section: Vol 18 2005 Aspergillus Infections In Transplant Recipientmentioning
confidence: 99%
See 1 more Smart Citation
“…An exception may be in patients with hematologic disorders in which neutropenia may be reversed. Successful treatment of primary cutaneous aspergillosis associated with neutropenia has been associated with reversal of neutropenia by use of granulocyte colony-stimulating factor (G-CSF) (115). Amphotericin preparations or voriconazole would be the preferred initial therapy.…”
Section: Vol 18 2005 Aspergillus Infections In Transplant Recipientmentioning
confidence: 99%
“…Therapy was switched to caspofungin, with dramatic and sustained improvement. Numerous reports have demonstrated that postsurgical wound infection requires aggressive surgical intervention in addition to antifungal drugs for successful resolution (45,115). The surgery may be as aggressive as limb amputation or extensive debridement of the kind seen in cases of necrotizing fasciitis.…”
Section: Vol 18 2005 Aspergillus Infections In Transplant Recipientmentioning
confidence: 99%
“…4,18 The accurate identification of Fusarium species, Paecilomyces lilacinus, and Acremonium species is of practical importance, because they often are resistant to several of the available antifungal agents. Selection of initial antifungal drug therapy and possible inclusion of surgical treatments may depend on the identity of the fungus, 21 " 23 and early specific antifungal therapy is more likely to lead to a positive clinical outcome. Definitive diagnosis of etiology in hyalohyphomycosis requires culture for the identification of the offending organism.…”
Section: Microbiology and Infectious Diseasementioning
confidence: 99%
“…22 ' 23,34 Although culture remains the standard for identification of the causative agents of hyalohyphomycosis, presumptive identification of these fungi in histologic sections is of value for several reasons. Histology results can be obtained in less than 24 hours, whereas a preliminary culture identification may require several days.…”
Section: Vol Myces and Acremonium Speciesmentioning
confidence: 99%
“…The therapy of localized fusariosis is important to prevent progression to disseminated fusariosis and includes surgical excision and systemic antifungal therapy. 6,10 However, the prompt treatment of disseminated fusariosis is unclear. 3 Fusarium species are resistant to most antifungal drugs.…”
Section: Case Reportmentioning
confidence: 99%